Regional policy beyond 2000: learning as device - van GEENHUIZEN, Marina; NIJKAMP, Peter (European Spatial Research and Policy, 1999)
The region has now widely been recognised as a principal setting for knowledge creation and use. The paper sets out an integrated framework of activities thai underlie knowledge-based economic growth in a regional setting, with an emphasis on the role of tacit knowledge creation and transfer. In this context, it discusses various potential policy ingredients. Furthermore, participatory policy approaches and scenario development are presented as policy tools thai match with the multi-actor situation and the multi-faceted uncertainty in the field. The paper concludes with a few recommendations for future research.